Microwave processing of cement and concrete materials - towards an industrial reality? - Buttress, A.J.; Jones, D.A.; Kingman, S.W. (Elsevier, 2015)
Each year a substantial body of literature is published on the use of microwaves to process cement and concrete materials. Yet to date, very few if any have lead the realisation of a commercial scale industrial system and is the context under which this review has been undertaken. The state-of the–art is evaluated for opportunities, and the key barriers to the development of new microwave-based processing techniques to enhance production, processing and recycling of cement and concrete materials. Applications reviewed include pyro-processing of cement clinker; accelerated curing, non-destructive testing and evaluation (NDT&E), and end-of-life processing including radionuclide decontamination.